Flexible Germanium (Ge) devices for various applications in Internet of Things (IoT) era - Dong, Wenyu (Nanyang Technological University, 2022)
In this final year project, we fabricated Germanium nanomembrane of 270 nm on a flexible substrate by transfer printing method. Based on this thin film, we performed tensile and compressive strain analysis as well as Raman-strain relation investigation. Also, the strain relaxation advantage brought by transfer printing method was observed during strain characterization. Then the flexible Germanium thin film was further processed to flexible Germanium based metal-semiconductor-metal photodetector. Dark current analysis with temperature and bending variations were conducted. The measured room temperature dark current density is at a low level, around 0.426 A cm-2 at 1 V, indicating that good quality flexible Ge thin film photodetector was achieved. Discussions on dark current mechanisms based on ideality factor and activation energy, as well as paper study on the strain-energy bandgap relation of our fabricated device are covered in the report,